An open-source based toolchain for the georeferencing of old cadastral maps - Follin,Jean-Michel; Fahrasmane,Maïté; Simonetto,Élisabeth (PeerJ Preprints, 2016)
More and more historical data are available on the web. In France, old cadastral maps are regularly published by the “départements”. Such material is relevant to various applications (on-the-field search of specific objects such as old boundary stakes, historical studies of demography, human activities, land cover…). The GeF laboratory is working on the development of a complete methodological toolchain to vectorise, correct and analyse cadastral parcels and their evolution, using open source software and programming language only (QGIS, GDAL, Python). This article details the use of a part of this toolchain - georeferencing old cadastral data - on parcels located near the Loir river, in two villages of southern Sarthe: Vaas and Aubigné-Racan. After a presentation of our methodological toolchain, we will discuss our first results.
Keywords: QUALITY ASSESSMENT; OLD CADASTRAL MAPS GEOREFERENCING; GEOMETRIC TRANSFORMATION